A review of mental health and wellbeing measures for universal secondary school screening. Issue 2 (3rd April 2021) - Waite, Michael; Atkinson, Cathy
ABSTRACT: The mental health and wellbeing of children and young people is an area of great concern for those within education and health sectors, with young people reported to be especially at risk during adolescence. This has resulted in increasing demand for measures which can identify children and young people at risk of developing mental health difficulties, in order for appropriate and early intervention to be implemented. Previous literature highlights the large numbers of measures available, but guidance on which might be most appropriate for school use is limited. This review identified 10 measures which could be used for universal secondary school screening, from the Anna Freud National Centre for Children and Families (AFNCCF) and the Child Outcomes Research Consortium (CORC) toolkit. Measures were evaluated in relation to their implementation, psychometric properties and quality; and to how well items measured domains identified by the National Institute of Clinical Excellence (NICE) domains of mental health and wellbeing. Findings indicated that the Good Childhood Index, KIDSCREEN-27, Stirling Children's Wellbeing Scale and the Warwick and Edinburgh Mental Health Scale are all suitable measures for universal secondary school screening of young people's mental health and wellbeing, as defined by NICE.